Application prospect of Traditional Chinese Medicine in periodontitis (探讨中医药在牙周炎中的应用前景) - (李瑛); FEN Lu (冯露); LEI Zhirui (雷志蕊); TAN Xin (谭欣); JIAO Yangliu (焦杨柳); WANG Lin (王琳) (Journal of International Translational Medicine Limited, 2022)
Based on the literature review and analysis, this article elaborated the research background, the current situation and results of Traditional Chinese Medicine in the treatment of periodontitis, so as to explore the application prospect of TCM in the treatment of periodontitis. (本文总结近年来中医药在牙周炎治疗中的应用现状, 对牙周炎中医药治疗的研究背景、现状发展、治疗效果等进行阐述, 并探讨中医药在牙周炎治疗中的应用前景, 以期为临床治疗牙周炎提供更多参考。)